PENGARUH SOSIAL EKONOMI ORANG TUA TERHADAP MOTIVASI SISWA DALAM MELANJUTKAN PENDIDIKAN KE PERGURUAN TINGGI - ANDI FIRWANSYAH; MUHAMMAD HASAN; TUTI SUPATMININGSIH; M. IHSAN SAID A; THAMRIN TAHIR (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2022)
The aim of this study is to provide parents and their children with a better understanding of the influence of their children's motivation to pursue higher education. This study uses a quantitative research methodology. Data collection is done through observation, survey, and documentation. A total of 230 students from SMAN 1 Benteng Selayar class XII participated in the lesson, and a sample representing 70 students from class XII IPA and XII IPS was selected to take part in the lesson. Data analysis used multiple linear regression analysis. Based on the findings of this study, two factors (X) have a significant influence on students' learning motivation (Y).